Panencephalopathic Creutzfeldt‐Jakob Disease with Distinct Pattern of Prion Protein Deposition in a Patient with D178N Mutation and Homozygosity for Valine at Codon 129 of the Prion Protein Gene. (27th November 2013) - Marcon, Gabriella; Indaco, Antonio; Di Fede, Giuseppe; Suardi, Silvia; Finato, Nicoletta; Moretti, Valentino; Micoli, Sandro; Fociani, Paolo; Zerbi, Pietro; Pincherle, Alessandro; Redaelli, Veronica; Tagliavini, Fabrizio; et al.
Abstract Prion diseases include sporadic, acquired and genetic forms linked to mutations of the prion protein (PrP) gene (PRNP). In subjects carrying the D178N PRNP mutation, distinct phenotypes can be observed, depending on the methionine/valine codon 129 polymorphism. We present here a 53‐year‐old woman with D178N mutation in the PRNP gene and homozygosity for valine at codon 129. The disease started at age 47 with memory deficits, progressive cognitive impairment and ataxia. The clinical picture slowly worsened to a state of akinetic mutism in about 2 years and the disease course was 6 years. The neuropathologic examination demonstrated severe diffuse cerebral atrophy with neuronal loss, spongiosis and marked myelin loss and tissue rarefaction in the hemispheric white matter, configuring panencephalopathic Creutzfeldt‐Jakob disease. PrP deposition was present in the cerebral cortex, basal ganglia and cerebellum with diffuse synaptic‐type pattern of immunoreactivity and clusters of countless, small PrP deposits, particularly evident in the lower cortical layers, in the striatum and in the molecular layer of the cerebellum. Western blot analysis showed the presence of type 1 PrPSc (Parchi classification). These findings underline the clear‐cut distinction between the neuropathological features of Creutzfeldt‐Jakob disease associated with D178N PRNP mutation and those of fatal familial insomnia.